2015
DOI: 10.1111/btp.12193
|View full text |Cite
|
Sign up to set email alerts
|

Amazonian Dark Earth Shapes the Understory Plant Community in a Bolivian Forest

Abstract: Amazonian Dark Earths (ADE) are the result of human modification of the Amazonian landscape since pre-Columbian times. ADE are characterized by increased soil fertility compared to natural soils. In the Amazonian forest, soil fertility influences understory herb and fern species composition. However, little research has been done to evaluate the effect of ADE on the composition of the understory community. We evaluated the effects of ADE and soil in 36 plots (150 m 9 4 m) established in a Bolivian moist forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 52 publications
1
27
0
1
Order By: Relevance
“…The increase in palm abundance is also visible in soil profiles of archaeological sites across the region Watling et al, 2017b), suggesting that past societies enriched the forest with useful palms to improve food production. Today, useful and domesticated palms are dominant in southwestern Amazonian forests (Levis et al, 2017b), growing on abandoned pre-Columbian mounds, anthropogenic soils and geoglyphs created by past management practices (Erickson and Balée, 2006;Quintero-Vallejo et al, 2015;Levis et al, 2017b;Watling et al, 2017b). Many palm species were found in most of the forest patches investigated here, suggesting long-term human management.…”
Section: Swiddensmentioning
confidence: 76%
See 2 more Smart Citations
“…The increase in palm abundance is also visible in soil profiles of archaeological sites across the region Watling et al, 2017b), suggesting that past societies enriched the forest with useful palms to improve food production. Today, useful and domesticated palms are dominant in southwestern Amazonian forests (Levis et al, 2017b), growing on abandoned pre-Columbian mounds, anthropogenic soils and geoglyphs created by past management practices (Erickson and Balée, 2006;Quintero-Vallejo et al, 2015;Levis et al, 2017b;Watling et al, 2017b). Many palm species were found in most of the forest patches investigated here, suggesting long-term human management.…”
Section: Swiddensmentioning
confidence: 76%
“…The persistent effect of pre-Columbian plant domestication on modern forest composition has been revealed in Amazonian old-growth forests (Junqueira et al, 2017;Levis et al, 2017b), secondary forests (Junqueira et al, 2010) and even in highly dynamic homegardens growing in archaeological sites . Domesticated species adapted to stable soil conditions created by management practices, such as TPI, may persist for a long time after abandonment (Quintero-Vallejo et al, 2015). This may explain why domesticated palms dominate modern forests growing on pre-Columbian mounds, anthropogenic soils and geoglyphs abandoned more than 400 years ago (Erickson and Balée, 2006;Quintero-Vallejo et al, 2015;Watling et al, 2017b).…”
Section: Swiddensmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative resource allocation to root depth on differing soil types is largely unknown for Amazonian trees and could be an important determinant of drought resistance (Asner and Vitousek 2005). Seedling recruitment has been shown to be lower on ADE sites and was attributed to Ca toxicity and nutrient imbalances (Quintero-Vallejo et al 2015), and this could contribute to differences in species composition. Others have suggested that ADE abandonment resulted in mineralization of organic C and nutrient leaching, thus reducing overall nutrient content and humus in the soil and potentially influencing forest structure (Neves et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In parts of the Amazon basin, pre-Columbian soil amendments (terra preta do indio) are decisive for soil nutrient availability today (Glaser & Birk 2012). It is conceivable that effects related to ancient logging and soil nutrient amendments may still influence floristic composition and species responses, not only at the local scale as shown by Quintero-Vallejo et al (2015) but also at a regional scale. Future studies on the physiological mechanisms underlying inter-or infra-specific trade-offs along edaphic gradients should attempt to encompass terra preta as an important confounding factor, but also clarify the anthropogenic influence on present-day palm distributions in Amazonia.…”
Section: H Y P E R D O M I N a N T C A N O P Y P A L M Smentioning
confidence: 99%